Psychological well-being of future specialists in the integrated educational environment and the factors of its formation - Serdiuk, Liudmyla (Social Welfare: Interdisciplinary Approach, 2011)
This paper deals with the factors affecting the psychological well-being of the person; the intensity of indexes of psychological well-being of personalities of both students with disabilities and healthy students in integrated groups has been analyzed: self-relationship, self-realization, and orientations of life-sense, interrelation of the past, present and future in the structure of psychological time of personality life have been discussed.The students with disabilities have more expressed demand in support and positive attitude to them. The reliable differences of a number of indexes of self-realization have been found, such as spontaneity (p
Keywords: Psychological well-being of the personality; self-attitude; self-actualization; life goals; values; temporary perspective